Doctors' views of disulfiram and their response to relapse in alcohol-dependent patients, Free State, 2009 - Paulina M. van Zyl (AOSIS, 2016)
Background: Disulfiram is the oldest and best known drug to prevent relapse after detoxification from alcohol. Effective use of the drug is dependent on stringent monitoring and high levels of external motivation. Doctors' perceptions about the drug have not been investigated extensively. Aim: We investigated the perceptions and practices of doctors involved in relapse prevention in alcoholics with regard to disulfiram and their response to relapse. Setting: The study population consisted of 60 doctors from the Free State Province, involved in the follow-up of alcoholics across various work settings. Methods: A cross-sectional descriptive study design was used, and data collection involved the use of a questionnaire and semi-structured interviews. Quantitative results are presented in figures and percentages to provide a background for the qualitative findings that are clustered in themes. Results: A quarter of participants did not prescribe disulfiram, another quarter prescribed disulfiram routinely after detoxification, and half of them prescribed it for selected cases only. Subject to affordability, selection of disulfiram was mainly determined by the perceived level of the patient's motivation. External motivation sometimes took the form of threats of bodily harm or death caused by drinking. Some participants regarded relapse as confirmation of poor motivation and even a valid reason for terminating the doctor-patient relationship. Conclusion: Doctors perceive disulfiram as a psychological tool to induce motivation through creating fear of drinking. Failure and success are perceived as related to the level of motivation. These perceptions could be unfair as biological factors in inter-patient variability in response are ignored.